Women's rights and misogyny in Brazil: An interview with Debora Diniz. Issue 2 (3rd April 2020) - BÄHRE, ERIK; DINIZ, DEBORA
Abstract : In 2018 anthropologist and feminist Debora Diniz appeared as an expert witness in a Supreme Court hearing that addressed decriminalizing abortion. After receiving death threats, she was placed under police protection and forced to go into hiding. The police discovered that a right‐wing extremist gang plotted an attack against her, and Diniz had to go into exile abroad, a fate she shares with several other academics working on women's rights and economic and racial inequalities. In this interview, Diniz reflects on the Brazilian political climate and its consequences for academics, freedom, women's rights and healthcare.